PENGARUH CORPORATE GOVERNANCE DAN FIRM SIZE TERHADAP FINANCIAL DISTRESS (Studi pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia periode 2017-2019) - Gaos, Robi Ridhayatul; Mudjiyanti, Rina (Kompartemen : Jurnal Ilmiah Akuntansi, 2021)
This study aims to find empirical evidence of the influence of corporate governance and firm size on financial distress. The sample used in this study is a banking company listed on the Indonesia Stock Exchange (BEI) for the 2017-2019 period. The sampling technique used was purposive sampling and obtained a sample of 40 samples that met the criteria. The data analysis technique used is multiple regression analysis. The financial distress criteria in this study measured using the Z-score in Altman’s financial distress prediction model. Based on the study results, it can be concluded that managerial ownership, the board of commissioners, and the audit committee have no effect on financial distress, while the board of directors has a positive and significant effect on financial distress and firm size has a negative and significant effect on financial distress.